Efficacy of Scattering Application and Paint-on Application of Insecticide in Controlling Housefly on a Broiler Farm - Ramoncito Cenon T. Asuncion; Listya Purnamasari; Joseph P. Olarve; Joseph F. Dela Cruz (Research Centre of Inorganic Materials and Complexs, 2022)
The study was performed to determine the efficacy of dinotefuran in controlling housefly (Musca domestica) infestation on a commercial broiler farm. The efficacy of the two modes of application of the insecticide was compared to thiamethoxam. The experiment was divided into two groups with five treatments (T) and three replicates per treatment. The first group was scatter application composed of T1: control, T2: dry 20 g dinotefuran, T3: wet 20 g dinotefuran, T4: dry 20 g thiamethoxam, and T5: wet 20 g thiamethoxam. The second group was a paint-on application composed of T1: control, T2: 10 g dinotefuran with 10 g sugar, T3: 20 g dinotefuran, T4: 10 g thiamethoxam with 10 g sugar, and T5: 20 g thiamethoxam. Dead flies were counted after 15, 30, 60, and 120 minutes post-application. In the scatter group, the control was significantly different from dinotefuran and thiamethoxam, but no significant differences were observed between dinotefuran and thiamethoxam. Dinotefuran treatments from paint-on were significantly different from the other three treatments. Lastly, wet dinotefuran from the scattering bait group and dinotefuran treatments from paint were not significantly different. Wet and paint-on treatments of dinotefuran were effective for fly control in broiler farms.